Pricing Optimal Outcomes in Coupled and Non-Convex Markets: Theory and Applications to Electricity Markets - Ahunbay, Mete Şeref; Bichler, Martin; Knörr, Johannes (Operations Research, 2025)
The clearing of nonconvex markets poses unique challenges. The canonical market clearing, a Walrasian equilibrium, needs not exist when participants’ preferences display nonconvexities, for example, due to technical constraints. Then market clearing prices might not exist, and side payments may be required to compensate losses. Electricity markets are a prime example. Market operators in the United States use heuristic pricing rules to compute market prices; the magnitude of the side payments, potential lost opportunity costs, and the quality of network congestion signals in prices have all become a concern. In “Pricing Optimal Outcomes in Coupled and Non-Convex Markets: Theory and Applications to Electricity Markets,” Ahunbay, Bichler, and Knörr propose a multiobjective framework for pricing such markets. The design goals are shown to be inherently conflicting but may be balanced against each other through traditional methods in multiobjective optimization. Pricing rules used in practice are identified as prices for a suitably convexified market, which motivates a novel pricing method that drastically reduces side payments while maintaining congestion signals in realistic test cases.